Investigation on the structure and thermoelectric properties of CuxTe binary compounds. Issue 3 (2nd January 2019) - Mukherjee, Shriparna; Chetty, Raju; Madduri, P. V. Prakash; Nayak, Ajaya K.; Wojciechowski, Krzysztof; Ghosh, Tanmoy; Chattopadhyay, Kamanio; Suwas, Satyam; Mallik, Ramesh Chandra
Abstract : The thermal conductivity of Cu2 Te is around 4 W m −1 K −1 at 300 K with low C p values. Abstract : Cu2 Te is a superionic conductor that belongs to the Phonon Liquid Electron Crystal class of thermoelectric (TE) materials. Despite the simple chemical formula, the crystal structures and phases in the Cu2 Te system have not been understood properly. In this work, we study the structural and TE properties of Cu2 Te (CT2), Cu1.6 Te (CT1.6) and Cu1.25 Te (CT1.25). The samples were synthesized via a solid-state reaction method. Powder X-ray diffraction analysis revealed that the samples have different crystal structures depending upon the Cu : Te stoichiometry. The elemental compositional analysis showed that all the samples are copper deficient. This is due to the precipitation of metallic copper on the surface of the ingot arising from the thermal dissociation of Cu2 Te. The transport properties were measured in the temperature range 300 K–600 K. The electrical conductivity ( σ ) decreases with an increase in temperature indicating a metal-like behaviour for all the samples. The positive Seebeck coefficients ( S ) for all the samples indicates that majority charge carriers are holes. The sample CT2 has a higher S (29.5 μV K −1 at 573 K) and a lower σ (2513 S cm −1 at 573 K) due to a lower carrier (hole) concentration compared to the other two samples. With the increase in Cu deficiency, the hole concentration increases, and this leads to higher electronic thermal conductivity in the samples CT1.6 and CT1.25. The maximum thermoelectric figure of merit of 0.03 at 524 K is achieved for the sample CT2 owing to its higher power factor (0.24 mW m −1 K −2 ) and lower thermal conductivity (3.8 W m −1 K −1 ). The present study bridges the gap between the theoretical predictions and experimental observations involving the various possible structures in this system. Furthermore, we have shown that the Cu vacancies are detrimental to the thermoelectric performance of Cu2 Te.